Enriching the Curriculum with Pennsylvania German. Issue 1 (25th May 2016) - Meindl, Joerg
Abstract : The German classroom should prepare students for the linguistic diversity of the target culture, including regional varieties and German spoken outside of the D‐A‐CH region. Because textbooks do not often include materials on regional varieties, this article presents a model to incorporate Pennsylvania German (PG) into the curriculum. The model does not aim on learning PG but employs PG to support the acquisition of Standard German and the development of language awareness. Furthermore, PG can be used as a basis for lessons on culture, critical thinking, and intercultural competence. Teachers can implement the model without PG experts or adding large amounts of content to the classroom. The article presents basic knowledge about PG, its speakers, and their cultural context, as well as information on easily accessible PG texts and dictionaries. Furthermore, the article outlines learning goals and provides suggestions for lessons. An appendix lists readily available resources for more information on Pennsylvania German culture.